Postulaty "poznaj samego siebie" i "bądź sobą" jako przykład komplementarności doradztwa filozoficznego i coachingu = The postulates of "know yourself" and "be yourself" as an example of the complementarity of philosophical counseling and coaching - Dudek, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The analyzes presented above concerning the mechanisms of each individual indicate their close connection with the understanding of human nature, the motivational system, personal subjectivity, its identity and coherence. The different meanings that we give to the postulates "know yourself" and "be yourself" are reflected in the solutions and projects present in the philosophical tradition, with particular emphasis on the psychology of morality. Therefore, there is a correlation between the goals pursued in coaching and the tasks of philosophical counseling. Paying attention to this regularity should be one of the conditions of professionalism in the profession of a coach.
Keywords: psychologia moralności; coaching; podmiot moralny; motyw; pragnienie; natura ludzka; tożsamość osobowa; psychology of morality; moral subject; motive; desire; human nature; personal identity